Empire and righteous nation : 600 years of China-Korea relations - Westad, Odd Arne (The Belknap Press of Harvard University Press, 2021)
"In a concise, trenchant overview, Odd Arne Westad explores the cultural and political relationship between China and the Koreas over the past 600 years. Koreans long saw China as a mentor. The first form of written Korean employed Chinese characters and remained in administrative use until the twentieth century. Confucianism, especially Neo-Confucian reasoning about the state and its role in promoting a virtuous society, was central to the construction of the Korean government in the fourteenth century. These shared Confucian principles were expressed in fraternal terms, with China the older brother and Korea the younger. During the Ming Dynasty, mentor became protector, as Korea declared itself a vassal of China in hopes of escaping ruin at the hands of the Mongols. But the friendship eventually frayed with the encroachment of Western powers in the nineteenth century. Koreans began to reassess their position, especially as Qing China seemed no longer willing or able to stand up for Korea against either the Western powers or the rising military threat from Meiji Japan. The Sino-Korean relationship underwent further change over the next century as imperialism, nationalism, revolution, and war refashioned states and peoples throughout Asia. Westad describes the disastrous impact of the Korean War on international relations in the region and considers Sino-Korean interactions today, especially the thorny question of the reunification of the Korean peninsula. Illuminating both the ties and the tensions that have characterized the China-Korea relationship, Empire and Righteous Nation provides a valuable foundation for understanding a critical geopolitical dynamic"--